Bottlenecks and good practices of DNSH implementation in Cohesion Policy: a comparison between rural and urban areas - Medeiros, E. (2024)
The ‘Do No Significant Harm’ principle (DNSH) seeks to ensure that European Union policies and European cohesion policy achievements comply with the objective of not significantly harming the environment and climate. The inclusion of an EU principle like the DNSH can increase the administrative burden on Managing Authorities. However, it can deliver positive impacts in modernising and enhancing the effectiveness of public bodies regarding policy monitoring and evaluation frameworks. In some cases, like Finland, the proposed DNSH evaluation methodology is detailed and elaborate. Other Member States, like Portugal, Italy, and Belgium, are more practical in their approach to assessing DNSH. Countries have different administrative capacity levels to assess ECP funds and requirements. Harmonising and simplifying the implementation of the DNSH principle through increased clarity in the requirements and a harmonised policy evaluation framework is recommended. This simplification process applies to the legal basis for the inclusion of the DNSH principle across the different instruments and the DNSH policy evaluation methodologies across EU Member States, which can allow an overall comparison of the implementation of this principle